Activation of rift oblique and rift parallel pre-existing fabrics during extension and their effect on deformation style: Examples from the rifts of Thailand - Morley C.K. (2014)
The Tertiary rift basins of Thailand have been previously interpreted in terms of strike-slip faulting. However, many of the trends oblique to the N-S orientation of the rift system appear to be inherited passive fabrics in the pre-rift, not active oblique strike-slip faults. Well developed N-S, NE-SW and NW-SE fabrics from Palaeozoic and Mesozoic orogenies exerted a strong influence on both Tertiary strike-slip and normal faults. Extensional fault systems are influenced in a number of ways by oblique pre-existing fabrics: these include (1) oblique orientation of faults, (2) preferred main fault and splay orientations oblique to the regional extension direction, (3) the location, geometry and style of transfer zones, and (4) fault linkage and displacement patterns. At high angles to the extension direction (about 45-50°) oblique extensional faults retain an essentially extensional, half graben character. Folds, thrusts, and inversion anticlines appear to be features associated with the compressional tips of individual and en-échelon compressional stepping-geometry, oblique extensional faults. In the Gulf of Thailand fabric inheritance from both the pre-rift section and syn-rift units has exerted an influence on the conjugate fault sets in the post-rift section. Experimental modelling has reproduced some key aspects of oblique extension, emphasising the degree of oblique opening as the major control on fault geometry and evolution. Equally, if not more important, is the number, relative strength, dip, strike, spacing, and type (pervasive or discrete) of fabric element. © 2004 Published by Elsevier Ltd.